التوجيه الصوتي للقراءات القرآنيَّة في كتاب [ فتح الرحمن في تفسير القرآن ] للإمام مجير الدين العليمي من أوَّل سورة يونس إلى آخر سورة يوسف (Comprehensive Journal of Science, 2026)
This study aims to highlight the phonetic dimension of the Qur’anic readings cited by Imam Mujir al-Din al-‘Alimi (may Allah have mercy upon him) in his book Fath al-Rahman fi Tafsir al-Qur’an, and to demonstrate his efforts in presenting, interpreting, and employing these readings to enrich meaning.The study adopts the descriptive-analytical method by collecting the readings mentioned by al-‘Alimi, analyzing their phonetic orientation, and identifying the phonetic phenomena reflected in them.The research consists of an introduction and two main sections. The first section (a preliminary chapter) introduces Imam Mujir al-Din al-‘Alimi. The second section examines the phonetic orientation of the Qur’anic readings in Fath al-Rahman fi Tafsir al-Qur’an. It is divided into five subsections: assimilation (idgham), phonetic substitution (ibdal), vowel harmony (ittiba‘), imalah, and gemination and lenition (tashdid and takhfif). The study concludes with a summary of the findings, followed by footnotes and a list of references upon which the research is based.
Keywords: Al-‘Alimi, phonetic orientation, Qur’anic readings, Fath al-Rahman